Managing dams challenges in a time of change : proceedings of the 16th Conference of the British Dam Society at the University of Strathclyde from 24-26 June 2010 - Pepper, A. T. (Thomas Telford, 2010)
The proceedings of the conference Managing dams covers a wide range of topics of direct relevance to all who are involved in the engineering and management of dams and reservoirs.